The nutritional quality of herbaceous legumes on goats: Intake, digestibility and nitrogen balances - Ginting, Simon P; Tarigan, Andi (Indonesian Journal of Animal and Veterinary Sciences, 2005)
The availability of forages is a critical factor that determine the sustainability of the animal-plantation production system. In this typical production system, cover crops could be an important sources of forages to support the animal production. The study is aimed to evaluate the nutritional quality (chemical compositions, intake, digestibility and N balances) of herbaceous legumes namely Arachis pintoi and Arachis glabrata having potential for used as alternative cover crops in plantation. Centerocema pubescens, a conventional cover crops used in plantation, was used as control. Twenty-one mature male goats (16-18 kg) were used in this experiment. The animals were put in individual metabolism cages, divided into three groups (7 animal per group) based on the body weight, and were randomly allocated into one of the three forages. The experiment was run in a Completely Randomized Design. The animals were allocated to an adaptation period for 14 days, followed by intake measurement for 5 days and fecal and urine collection for the next 7 days. During the fecal and urine collection forages were offered at 90% of the maximum intake. Chemical analyses showed that the DM and OM contents were relatively equal among the forages, but the crude protein content of C. pubescens (23.56%) are relatively higher than those of A. pintoi (16.94%) or of A. glabrata (15.19%) The fiber (NDF) content was also relatively higher in C. pubescens (59.37%) than in A. pintoi (16.94%) or A. glabrata (41.50%). The forage intake was highest (P<0.05) in goats fed C. pubescens (493 g/d), and were not different (P>0.05) between goats fed A. pintoi (466 g/d) or A. glabrata (453 g/d). A similar trend was seen when intake was expressed as % BW (3.80, 3.50 and 3.40, respectively) or as g/kg BW0.75 (42.4, 39.5 and 38.4, respectively). The digestion coeficient of DM (81.3%) or OM (83.5%) were highest (P<0.05) in A. pintoi and were not different (P>0.05) between A. glabrata (71.9 and 73.2%, respectively) and C. pubescens (73.7 and 74.2%, respectively). The trends were the same with the digestion coeficient of ADF and the energy. The ADF digestibility were 67.8, 55.9 and 54.5% in A. pintoi, A. glabrata and C. pubescens, respectively). The energy digestibility were 81.8, 67.5 and 69.4% in A. pintoi, A. glabrata and C. pubescens, respectively. The N balances were positive in goats fed these three forages, but the highest (P<0.05) N retention was observed in goats offered C. pubescens (17.7 g/d) as compared to those fed A. pintoi (9.4 g/d) or A. glabrata (7.7 g/d). The higher intake level in goats fed C. pubescens and its higher N content seemed to be the main reason for the highest N retention. It is concluded that based on these nutritive parameters, C. Pubescens has superior nutritive quality compared to A. pintoi and A. glabrata, while the A. pintoi seemed to be better than the A. glabrata. Â  Â  Key Words: Legumes, Cover Crops, Nutritive Quality, Goats